THE PROFESSIONAL ETICS ON THE PSYCOLOGISTS FORMATION: A BIBLIOGRAPHICAL AND DOCUMENTAL STUDY - Leiva, Juliene de Cassia [UNESP]; Lemes, Sebastiao de Souza [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2016)
A literature study was conducted in Scielo database, descriptive, in order to know how professional ethics theme is present in the training of psychologists. Data were analyzed in an articulated manner to ancillary documents such training as the National Guidelines for Training Psychologists and Code of Professional Ethics of Psychologist, pointing to the main challenges to be considered today, in such a context. It was also analyzed the Educational Psychology Course Design of a University Center in the state of Sao Paulo, which showed the operationalization of the structuring axes proposed by the guidelines, which partially cover the component professional ethics, with emphasis on procedural aspects and attitudinal the training of psychologists.
Keywords: Professional ethics; Training in psychology; Curriculum guidelines